If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3q + 6 = 20 Reorder the terms: 6 + 3q = 20 Solving 6 + 3q = 20 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 3q = 20 + -6 Combine like terms: 6 + -6 = 0 0 + 3q = 20 + -6 3q = 20 + -6 Combine like terms: 20 + -6 = 14 3q = 14 Divide each side by '3'. q = 4.666666667 Simplifying q = 4.666666667
| 6r^2+r=1 | | 26=3x+2x-9 | | x(x+7)+-12(x+7)=0 | | 9x(3x-20)=74 | | 49s^2-81d^2= | | 2(3n-3)=30 | | x(x+11)-18(x+11)=0 | | 9y^2-18y+5=0 | | -19.95+1.10x=18 | | 9y^2-9y+2=0 | | 12-5x-25x^2=0 | | -19.95+1.10x=-1.35 | | u^2+7a^2+6=0 | | 3ln(x+6)=15 | | 2=15z^2+2 | | M+3m+0.5m=36 | | 31n(x-6)=15 | | 81-3x=45 | | 4x+28=30 | | 4w-2w-w+w-w=18 | | 7x-4x-2x-x+x=16 | | 2+3x+1=6x | | 3(2-x)=6 | | 16h+5h-20h=14 | | 7a+a+3a-9a=6 | | 14x+20y=12775 | | 7a+a+3a-9a= | | 16z-15z=20 | | 5(x+4)=2x+20+2x | | 6q-2q=16 | | 2d+d=18 | | 4y^2+33y+23=0 |